EVALUTION OF HYDROCARBONIC RAW MATERIALS’ RESERVES OF THE CASPIAN REGION’S COUNTRIES - D. Kuramshin (Вестник университета, 2016)
The Caspian region plays the increasing role in world power in the modern conditions. At the same time, the role of the certain countries in power of the region is not identical. In the article reserve of hydrocarbonic raw materials in the countries of the region on main types of fuel are estimated and the main stages of forming of energy space of the region are defined.